2015
DOI: 10.1038/srep13854
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing synchrony by inhomogeneity

Abstract: We show that for two weakly coupled identical neuronal oscillators with strictly positive phase resetting curve, isochronous synchrony can only be seen in the absence of noise and an arbitrarily weak noise can destroy entrainment and generate intermittent phase slips. Small inhomogeneity–mismatch in the intrinsic firing rate of the neurons–can stabilize the phase locking and lead to more precise relative spike timing of the two neurons. The results can explain how for a class of neuronal models, including leak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 69 publications
(94 reference statements)
0
2
0
Order By: Relevance
“…A different body of work has shown that, for periodic oscillators, heterogeneity can in certain cases facilitate synchronization [27][28][29][30][31][32]. A natural question is then whether a similar effect would be possible for chaotic oscillators despite the fact that their dynamics exhibit sensitive dependence on parameters and that an invariant synchronization manifold no longer exists for nonidentical chaotic oscillators.…”
mentioning
confidence: 99%
“…A different body of work has shown that, for periodic oscillators, heterogeneity can in certain cases facilitate synchronization [27][28][29][30][31][32]. A natural question is then whether a similar effect would be possible for chaotic oscillators despite the fact that their dynamics exhibit sensitive dependence on parameters and that an invariant synchronization manifold no longer exists for nonidentical chaotic oscillators.…”
mentioning
confidence: 99%
“…These qualitatively different responses to stimulation lead to dramatically different synchronization patterns in neural networks. Previous studies have shown that, type I cells exhibit relatively poor propensity for synchronization under excitatory couplings, while type II cells are synchronized better 11,14,15 .…”
Section: Introductionmentioning
confidence: 95%